Development of the Pan African burn services directory. Issue 8 (December 2019) - Gibson, Cameron; Gallagher, James; Heffernan, Jamie
Highlights: First online directory of burn care providers in Africa. Interactive online map that is searchable, mobile-friendly, and publicly available. Continued recruitment of burn care providers to expand list. Abstract: Background: International burn societies in many parts of the world have created electronic registries of burn centers in their region. No such directory exists for the continent of Africa. Objective: To create the first electronic directory of burn care providers in Africa. Methodology: Emails were sent out to attendees of the Pan African Burn Congress and members of the Pan African Burn Society (PABS) asking if they would like to participate in the directory. Basic information about each burn site were obtained from respondents and compiled into the directory. An online interactive map was created and made available to the public. Results: 40 burn sites were identified across 14 different countries. The majority of burn sites are located in only 5 countries. The most common language spoken is English, followed by French, Amharic, and Afrikaans. Conclusion: This is the first known online directory of burn sites in Africa. Significant challenges exist identifying burn care providers in large portions of the continent.